The Incas - Davies, Nigel, 1920-2004 (Book collections on Project MUSE., 1995)
"Readable summary of the history, imperial infrastructure, mechanisms of control and integration, and other unique characteristics of the Inca Empire"--Handbook of Latin American Studies, v. 57.